Edukasi Kesehatan Media Audiovisual Dalam Upaya Peningkatan Literasi Siswa tentang Demam Berdarah Dengue - Misga, Nesdania; Siswanti, Heny; Jauhar, Muhamad (PT. Pubsains Nur Cendekia, 2025)
Background: Dengue fever (DF) is a tropical disease that remains a significant global public health concern. One of the contributing factors to its persistence is the lack of health literacy and public awareness. Health education programs implemented in schools can play a vital role in improving students’ knowledge about dengue fever prevention, promoting better hygiene practices, and ensuring that school environments remain free of mosquito breeding sites. Aim: This study aimed to determine the effect of audiovisual-based health education on elementary school students’ health literacy regarding dengue fever prevention. Method: A quasi-experimental pre–post-test design with a control group was employed. The study was conducted at SD Negeri Plaosan 01 in November 2024, involving 25 participants in each group selected through purposive sampling. Data were collected using a dengue fever prevention health literacy questionnaire, which demonstrated validity values ranging from 0.412 to 0.774 and a reliability coefficient of 0.828. Data were analyzed using the Wilcoxon Rank Test and the Mann–Whitney U test. Results: Audiovisual-based health education significantly improved the health literacy of elementary school students concerning dengue fever prevention. After the intervention, all students in the intervention group (100%) demonstrated good health literacy, compared to 92% in the control group. Statistical analysis revealed a significant difference between the two groups (p = 0.000; p < 0.05), indicating the high effectiveness of audiovisual media in enhancing students’ understanding. Conclusion: Audiovisual-based health education effectively increases students’ knowledge and awareness of dengue fever prevention. Students who have gained this knowledge are expected to apply preventive behaviors, such as maintaining environmental cleanliness, implementing the 3M Plus strategy, and promoting a healthy, mosquito-free environment.